Unilateral Atraumatic Expulsion of an Ectopic Pregnancy in a Case of Bilateral Ectopic Pregnancy - Victoria Sampson; Oluremi Mogekwu; Ammar Ahmed; Farida Bano (Case Reports in Obstetrics and Gynecology)
Ectopic pregnancy occurs in 1-2% of pregnancies. The fallopian tube is the most common site; however, bilateral tubal ectopic pregnancy is an extremely rare phenomenon, seen in approximately 1/200,000 pregnancies. It is usually the result of assisted reproductive techniques (ART). Ultrasound (USS) and serial beta-hCG levels have shown poor efficacy for accurate diagnosis. Laparoscopy is the diagnostic gold standard. The majority of cases are managed surgically with bilateral salpingectomy. A 26-year-old female presented to our early pregnancy unit with pain and vaginal bleeding at 5-week gestation after IVF. USS was inconclusive and her b-hCG levels rose with worsening pain; therefore, a decision was made for diagnostic laparoscopy. Although there was a clear right sided ectopic pregnancy, the left tube was swollen and therefore a methylene blue dye test was carried out to confirm blockage. Atraumatic milking, to expose the dye, expelled necrotic tissue which histology confirmed to be a second ectopic pregnancy. She made a good recovery with falling beta-hCG levels and left tubal preservation. As the use of ART increases, bilateral ectopic pregnancies will become more common. Novel and established techniques should be used to help confirm the diagnosis and assist in tubal preservation.